Tantangan Penerapan Inovasi Budaya Organisasi dalam Pengelolaan Alokasi Dana Nagari/Desa dalam Rangka Mewujudkan Pemerintahan Desa yang Baik - Handraini, Helti; Frinaldi, Aldri (YASIN, 2024)
Nagari/village funds are an important instrument that can be used to improve community welfare, reduce regional disparities, and strengthen local economic empowerment. However, in practice, the implementation of organizational culture innovation in nagari/village government structures is often faced with a number of complex challenges. Nagari/village leaders and officials who have skills in organizational culture innovation can help in developing a better nagari/village fund management system, such as using information technology in reporting and monitoring the use of funds, or applying the principles of good governance in decision making. This research uses a qualitative approach with descriptive methods to explore the challenges associated with implementing organizational culture innovation in managing nagari/village funds in order to achieve the goals of good nagari/village governance. A qualitative approach provides an appropriate framework for understanding in depth the cultural context of organizations at the nagari/village level and the dynamics involved in dealing with change. The research results show that the role of nagari/village leaders and officials is very crucial in encouraging the adoption and implementation of organizational culture innovations in managing nagari/village funds. Resistance to change is still a significant challenge faced by many nagari/villages in implementing organizational culture innovation. Factors such as discomfort with the status quo and lack of understanding of the benefits of innovation can hinder efforts to improve the effectiveness of nagari/village fund management.